PENANAMAN NILAI-NILAI MULTIKULTURAL MELALUI PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA PGRI 2 LAWANG - Cindy Ika Saraswati; Moh. Mansur Fauzi (STAI Ma'had Aly Al-Hikam Malang, 2024)
Indonesia is a pluralistic country because its own citizens consist of a variety of ethnicities, religions, languages, cultures, and different beliefs because of the many diversities that often many conflicts occur. So religious education is needed to create an attitude of tolerance, respect, and understanding. SMP PGRI 2 Lawang is a public educational institution with a lot of diversity in its students. For this reason, Islamic Religious Education is needed to foster multicultural values. This research aims to find out the multicultural values at SMP PGRI 2 Lawang through Islamic Religious Education and to find out the supporting and inhibiting conditions for the cultivation of multicultural values at SMP PGRI 2 Lawang through Islamic Religious Education. Qualitative research is the method used in this study. In collecting data, researchers used observation, interviews, and documentation. In analyzing the data, researchers used data reduction, data presentation, and conclusion. Testing the validity of the research data, researchers used triangulation and extended observation.